2019
DOI: 10.2337/db18-1050
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-Induced Transcription Factors Repress Vitamin D Bioactivation, a Mechanism for Vitamin D Deficiency in Diabetes

Abstract: Low 25-hydroxyvitamin D levels correlate with the prevalence of diabetes; however, the mechanisms remain uncertain. Here, we show that nutritional deprivationresponsive mechanisms regulate vitamin D metabolism. Both fasting and diabetes suppressed hepatic cytochrome P450 (CYP) 2R1, the main vitamin D 25-hydroxylase responsible for the first bioactivation step. Overexpression of coactivator peroxisome proliferator-activated receptor g coactivator 1-a (PGC-1a), induced physiologically by fasting and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 52 publications
(67 reference statements)
4
56
0
Order By: Relevance
“…This hormonal system functions as most steroid and thyroid hormones and regulates a very large number of genes involved in calcium and phosphate transport but also regulates a very large number of genes (up to 10% of all genes of the some organisms such as the zebrafish) not involved in ion transport or bone metabolism (reviewed in Bouillon and colleagues(1)).However, a few recent publications have challenged some aspects of our understanding of vitamin D metabolism including the concept of stable expression of the hepatic 25-hydroxylases. (2,3) We review these new data regarding CYP2R1, discuss their potential implications, and extend this review to examine the overall metabolism of vitamin D to explore whether old dogmas still hold today.Obesity and the metabolic syndrome are associated with low vitamin D status. (1) Prospective studies suggest that low nonepimeric 25OHD or increased 3-epi-25OHD concentrations are associated with higher risk for type 2 diabetes.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This hormonal system functions as most steroid and thyroid hormones and regulates a very large number of genes involved in calcium and phosphate transport but also regulates a very large number of genes (up to 10% of all genes of the some organisms such as the zebrafish) not involved in ion transport or bone metabolism (reviewed in Bouillon and colleagues(1)).However, a few recent publications have challenged some aspects of our understanding of vitamin D metabolism including the concept of stable expression of the hepatic 25-hydroxylases. (2,3) We review these new data regarding CYP2R1, discuss their potential implications, and extend this review to examine the overall metabolism of vitamin D to explore whether old dogmas still hold today.Obesity and the metabolic syndrome are associated with low vitamin D status. (1) Prospective studies suggest that low nonepimeric 25OHD or increased 3-epi-25OHD concentrations are associated with higher risk for type 2 diabetes.…”
mentioning
confidence: 99%
“…They also used the ratio of serum 25OHD to serum vitamin D concentrations as a marker of 25-hydroxylase activity and found a strong positive correlation between this ratio and liver mRNA expression of CYP2R1.Aatsinki and colleagues addressed a similar question about the origin of fairly systematic low serum 25OHD concentrations in diabetic subjects compared with their euglycemic controls, by studying high-fat-diet-induced obesity and type 2 diabetes in mice. (3) In addition, they also studied the effect of 24-hour fasting and of streptozotocin-induced type 1 diabetes. All these…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of ERRα expression are associated with a poor prognosis in breast cancer [21] while several reports have described ERRα as a predictive biomarker of response to endocrine therapy in the same setting [22][23][24]. Recent studies have described a novel cross-talk between ERRα and the vitamin D pathway in diabetes [25]. Astninski et al, indeed, demonstrated that the induction of CYP24A1 by fasting was regulated through a peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α)-ERRα-dependent mechanism, showing, for the rst time, a role for ERRα in the suppression of vitamin D signaling.…”
Section: Introductionmentioning
confidence: 99%